Reducing the environmental footprint of gastrointestinal endoscopy: European Society of Gastrointestinal Endoscopy (ESGE) and European Society of Gastroenterology and Endoscopy Nurses and Associates (ESGENA) Position Statement - Rodríguez de Santiago, Enrique; Dinis-Ribeiro, Mario; Pohl, Heiko; Agrawal, Deepak; Arvanitakis, Marianna; Baddeley, Robin; Bak, Elzbieta; Bhandari, Pradeep; Bretthauer, Michael; Burga, Patricia; Donnelly, Leigh; Eickhoff, Axel; Hayee, Bu'Hussain; Kaminski, Michal F.; Karlović, Katarina; Lorenzo-Zúñiga, Vicente; Pellisé, Maria; Pioche, Mathieu; Siau, Keith; Siersema, Peter D.; Stableforth, William; Tham, Tony C.; Triantafyllou, Konstantinos; Tringali, Alberto; Veitch, Andrew; Voiosu, Andrei M.; Webster, George J.; Vienne, Ariane; Beilenhoff, Ulrike; Bisschops, Raf; Hassan, Cesare; Gralnek, Ian M.; Messmann, Helmut (Endoscopy, 2022)
Climate change and the destruction of ecosystems by human activities are among the greatest challenges of the 21st century and require urgent action. Health care activities significantly contribute to the emission of greenhouse gases and waste production, with gastrointestinal (GI) endoscopy being one of the largest contributors. This Position Statement aims to raise awareness of the ecological footprint of GI endoscopy and provides guidance to reduce its environmental impact. The European Society of Gastrointestinal Endoscopy (ESGE) and the European Society of Gastroenterology and Endoscopy Nurses and Associates (ESGENA) outline suggestions and recommendations for health care providers, patients, governments, and industry. Main statements 1 GI endoscopy is a resource-intensive activity with a significant yet poorly assessed environmental impact. 2 ESGE-ESGENA recommend adopting immediate actions to reduce the environmental impact of GI endoscopy. 3 ESGE-ESGENA recommend adherence to guidelines and implementation of audit strategies on the appropriateness of GI endoscopy to avoid the environmental impact of unnecessary procedures. 4 ESGE-ESGENA recommend the embedding of reduce, reuse, and recycle programs in the GI endoscopy unit. 5 ESGE-ESGENA suggest that there is an urgent need to reassess and reduce the environmental and economic impact of single-use GI endoscopic devices. 6 ESGE-ESGENA suggest against routine use of single-use GI endoscopes. However, their use could be considered in highly selected patients on a case-by-case basis. 7 ESGE-ESGENA recommend inclusion of sustainability in the training curricula of GI endoscopy and as a quality domain. 8 ESGE-ESGENA recommend conducting high quality research to quantify and minimize the environmental impact of GI endoscopy. 9 ESGE-ESGENA recommend that GI endoscopy companies assess, disclose, and audit the environmental impact of their value chain. 10 ESGE-ESGENA recommend that GI endoscopy should become a net-zero greenhouse gas emissions practice by 2050.